Etika, Estetika, dan Dinamika dalam Novel Roro Mendut dan San Pek Eng Tay Serta Sumbangannya Dalam Pembelajaran Sastra Pada Program Studi PGMI STAIN Ponorogo - Puspidalia, Yuentie Sova (IAIN Ponorogo, 2016)
The literature is not a mitigated literary work which has no value. A literary work, such as novel, contains the moral values that exist in the life of society. The values of life can be used as learning materials. The appropriate choice of interesting materials can enhance students learning motivation and may lead them into better personalities. In this study, RoroMendut and San PekEngTay novels were analyzed the values of ethics, aesthetics, and social dynamics that might affect the literature learning in PGMI program, STAIN Ponorogo. In the course of Indonesian Language 2, there was a particular instructional objective called Indonesian language and literature appreciation.Â In order that students are able to appreciate the literature well, they need to be equipped with the knowledge and behavioral pattern of peoples lives. With knowledge of critical analysis to literature, they are expected to have adequate knowledge to respond the life artistically and imaginatively. This research was a descriptive study with qualitative approach. The analysis showed that the ethical, aesthetic, cultural and social dynamics in both novels could contribute to the study of literature, particularly in PGMI program-STAIN Ponorogo, which could be used as teaching materials of literary learning, particularly in the course of Indonesian Language 2 with the topic of literature appreciation.Â Ø¥Ù Ø§ÙØ§ÙØªØ§Ø¬Ø§Øª Ø§ÙØ£Ø¯Ø¨ÙØ© ÙÙØ³Øª ÙØªØ§Ø¨Ø§Øª ÙÙØ³ ÙÙØ§ Ù Ø¹ÙÙ Ø¨Ù ÙÙÙÙØ§ ÙÙÙ . ÙØ¹ÙÙ Ø³Ø¨ÙÙ Ø§ÙÙ Ø«Ø§Ù Ø§ÙØ±ÙØ§ÙØ©Ø ÙÙÙØ§ ÙÙÙ Ø§ÙØÙØ§Ø© ÙÙ Ø§ÙÙ Ø¬ØªÙ Ø¹. ÙÙÙ ÙÙ Ø£Ù ØªÙÙÙ ÙØ°Ù Ø§ÙÙÙÙ Ù ÙØ§Ø¯Ø§ Ø¯Ø±Ø§Ø³ÙØ©. ÙØ§Ø®ØªÙØ§Ø± Ø§ÙÙ Ø§Ø¯Ø© Ø§ÙØ¬Ø°ÙØ§Ø¨Ø© ÙØ±ÙÙÙ Ø¯ÙØ§ÙØ¹ Ø§ÙØ·ÙØ§Ø¨ ÙÙ Ø§ÙØªØ¹ÙÙÙ ÙÙØ¯ÙÙÙ Ø¥ÙÙ Ø£Ù ÙÙÙÙÙØ§ Ø£ÙØ±Ø§Ø¯Ø§ ØµØ§ÙØÙÙ. ØªÙØÙÙÙ ÙÙ ÙØ°Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø§ÙØ±ÙØ§ÙØ© Roro Mendut Â Ù San Pek Â Eng TayÙ Ù ØÙØ« Ø§ÙØ£Ø®ÙØ§Ù ÙØ¹ÙÙ Ø§ÙØ¬Ù Ø§Ù ÙØ¯ÙÙØ§Ù ÙØ§ØªÙÙ Ø§ Ø§ÙØ§Ø¬ØªÙ Ø§Ø¹ÙØ© Ø§ÙÙ Ø¤Ø«Ø±Ø© ÙÙ ØªØ¹ÙÙÙ Ø§ÙØ£Ø¯Ø¨ ÙÙ ÙØ³Ù PGMI ÙÙ Ø§ÙØ¬Ø§Ù Ø¹Ø© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© Ø§ÙØÙÙÙ ÙØ© ÙÙÙÙØ±ÙØºÙ. ÙÙ ÙØ°Ø§ Ø§ÙÙØ³Ù ØªÙØ¬Ø¯ Ù Ø§Ø¯Ø© Ø¯Ø±Ø§Ø³ÙØ©